Fluoxetine Induced Fecal Incontinence in a 9 Year Old Child with Autistic Spectrum Disorder: A Case Report - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2009)
Despite the dramatic rise in the use of selective serotonin reuptake inhibitors (SSRIs) in children and adolescents with pervasive developmental disorders (PDD) in recent years, the majority of studies of SSRI use in PDD population demonstrated lower tolerability compared to children without PDD. Among the adverse reactions to SSRI use, gastrointestinal adverse effects (GIS-AE) are common and usually reported to be mild and self limited. Children with PDD are shown to have higher rates of gastrointestinal symptoms including stool inconsistencies than the general childhood population and although not previously shown, they may be more vulnerable to severe GIS-AE of SSRIs. We present a case of a 9 year old girl with PDD not otherwise specified (PDD-NOS) who developed fecal incontinence (FI) in the treatment of fluoxetine which led to the discontinuation of the agent. Clinicians must be aware of severe GIS-AE when using SSRIs in children with PDD.
Keywords: Fluoxetine; Fecal incontinence; pervasive developmental disorders (SSRI); child; SEROTONIN REUPTAKE INHIBITORS; GASTROINTESTINAL SYMPTOMS; ADVERSE EVENTS; ADOLESCENTS; ANXIETY; DEPRESSION